Intervenções urbanas em espaços de desvalia. Transformar para valorizar. - Muniz, Maria águeda Pontes Caminha (2012)
The worldwide transformations that took place in the 20th century redefined the cities fate in this new century. The consolidation of urbanization, the technological revolution that fostered globalization, the economic restructuration and informalization, modified space and time concepts, bringing populations closer together and provoking political transformations. They made contemporaries cities protagonists of world events and as a consequence of such processes, worthlessness spaces appeared and cities all over the world started to bet on the strategy of acting in this problematic areas through initiatives aimed at promoting intentional transformations to obtain a multidimensional valorization urban, financial, environmental, cultural and social. In short, such urban initiatives intend to make cities more competitive, sustainable, creative, productive and fair. Also in Brazil, countless worthless spaces appeared in waterfronts, central areas, and deactivated industrial/urbanized areas, as well as in sub-used or misused areas lacking infrastructure and public services where it is imperative and urgent to perform urban initiatives. This research proposes as a thesis that urban initiatives, when carried out based on an adequate politicalinstitutional model, transform and give value to worthless spaces in their multiple dimensions, offering better quality of life to their residents and helping to fulfill the social role of the city. We intend to prove this thesis through the analysis of national and international cases and by introducing thoughts, critique and guidelines as a contribution to the improvement of the urban initiatives implementation processes, in particular to those regarding worthless areas of Brazilian cities